Notification Concerning the Title of a Church: Canon 1218 (Roman replies and CLSA advisory opinions 1999, 1999)
On February 12, 1999, the Congregation for Divine Worship and Discipline of the Sacraments published Notificatio de titulo ecclesiae, which concerned church titles and the designation of patrons. In his letter to the Most Reverend Joseph A. Fiorenza, Bishop of Galveston-Houston, and President of the National Conference of Catholic Bishops, 'His Eminence Jorge A. Cardinal Medina Estevez, Prefect of the Congregation, stated this Notification was being published to assist bishops, especially in the United States, in dealing with the difficulties which have arisen in relation to restructuring parishes. He noted that several cases, already handled by the Congregation, have been appealed to the Supreme Tribunal of the Apostolic Signatura where they await judgment. What follows are the official Latin text and an unofficial English translation.